Perubahan Titik Muatan Nol dan Muatan Negatif Abu Terbang Batubara akibat Penambahan Kotoran Ayam dan Waktu Inkubasi - AGUS HERMAWAN; SABARUDDIN SABARUDDIN; MASRI MASRI; RENIH HAYATI; WARSITO WARSITO (Jurnal Agroekoteknologi Tropika (Journal of Tropical Agroecotechnology), 2014)
ABSTRACT Changes in Point of Zero Charge and Negative Charge of Coal Fly Ash due to Chicken Manures Addition Fly ash, coal combustion residue of thermal power plants, has been regarded as a problematic solid waste all over the world. Due to the environmental problems created by large-scale fly ash generation, efforts are being made to recycle these materials, such as to improve soil fertility as an ameliorant. In the present study, the possibility to improving the status of point of zero charge (PZC) and negative charge in fly ash (FA) and chicken manure (CM) mixtures was investigated. Fly ash was mixed with chicken manure composition of 0, 25, 75, and 100 % FA (w/w basis) and incubated for 15, 30, 45, and 60 days. Treatments arranged in factorial completely randomized design with 3 replicates. The results showed that the compositions of FA-CM and incubation period significantly affect the status of TMN, negative charge, P sorption and available-P. The mix of 50% FA with 45 days incubation tend to have a lower PZC and P sorption and higher negative charge and P-available. This composition could be use as an amelioran to improve the soils chemical properties in terms to decrease PZC and increase negatif charge, and it is necessary for further research.   Keywords: chicken manure, coal fly ash, point of zero charge, negative charge